Hubungan Kecemasan dengan Motivasi Berprestasi Tim Putri Floorball Unesa dalam Menghadapi Kejuaraan Rektor Unesa Floorball Cup 2024 - Azizah, Rossiana Diah Nur; Pudjijuniarto (MAN Insan Cendekia Jambi, 2025)
This study aims to determine the relationship and how big the relationship is between anxiety and achievement motivation of Unesa women’s floorball team athletes in facing the 2024 Rector Unesa Floorball Cup championship. This quantitative descriptive method uses correaltion, the population on this study consisted of 15 Unesa women’s floorball team athletes, the sampling method used purposive sampling. The research instrument used a questionnaire with a likert scale, statistical data analysis techniques with the help of the SPSS version 22 application. The results of study showed that (1) There was a strong relationship between anxiety and achievement motivation in the women’s floorball team athletes before the match. The form of a significant relationship between these two variables is positive, which means that an increase in anxiety tends to be followed by an increase in achievement motivation in athletes. This means that achievement motivation increases along with the level of anxiety of athletes. Conversely, the lower the anxiety of the athlete, the lower the athletes achievement motivation. (2) The magnitude of the relationship between anxiety and the achievement motivation of athletes from the Unesa women’s floorball team is 55.2% which indicates a moderate category, while the remaining 44.8% is influenced by other factors not inclued in this study. The term moderate refers to a category of relationship that are not extreme, but are in the middle of the range of variable relationships. These result show that anxiety has significant, but not dominant, relationship with the athletes achievement motivation.